Effect of Types and Dosages of Foliar Fertilizers on Morphology and Production of Clitoria ternatea - Apriyani Nur Sariffudin; Nafiatul Umami; Bambang Suhartanto; Bambang Suwignyo; Kustantinah Kustantinah (Indonesian Center for Animal Research and Development (ICARD), 2021)
The aim of this study was to determine effect of types and dose levels of foliar fertilizers on morphology and production of Clitoria ternatea. This study was conducted from September to November 2020 at Forage Research Garden for Animal Feed and Pasture, Faculty of Animal Science, Gadjah Mada University, Yogyakarta. Materials used were Clitoria ternatea, liquid organic fertilizer of rabbit and gandasil D fertilizer. This study was designed in a Completely Randomized Design (CRD) with factorial pattern of 2x4. The fertilizer dosages were: 0,1.5,3.0 and 4.5 g/l/plot. The parameters measured were plant height, stem diameter, leaf area, number of branches, fresh and dry matter productions. Data were analyzed by the analysis of variance at 5%, with Duncan's Multiple Range Test (DMRT). Results showed that types of foliar fertilizers did not affect morphological characteristics and production of Clitoria ternatea (P>0.05), but the fertilizer dosages had significant effect (P<0.05) on morphological characteristics except for leaf area and production of Clitoria ternatea. The higher the dose level of foliar fertilizer the greater the plant height, stem diameter and number of branches. Dosage of 4.5 g/l/plot resulted in the highest plant height, stem diameter and number of branches each 160.02, 1.14 cm and 18.96 branches, respectively. Dosage of4.5 g/l/plot gave the highest fresh and dry matter production of 19.22 and 16.75 tons/ha. It is concluded that increasing the dosage level of foliar fertilizer up to 4.5 g/l/plot resulted in an increased quantity measures of several morphological characteristics and production.